An Analysis of Integrating Language Skills in Teaching Arabic to Non-Native Speakers - K. M. A. Ahamed Zubair (RADINKA JAYA UTAMA PUBLISHER, 2024)
This study explores the importance of integrating the four language skills- listening, speaking, reading, and writing teaching Arabic to non-native speakers, as opposed to the traditional methods that isolate these skills. The objective of this research is to demonstrate how an integrative approach to language instruction enhances learners’ overall proficiency and communicative competence. Using an analytical survey method, an electronic questionnaire was distributed to 120 students enrolled in the Post Graduate and Research Department of Arabic at The New College, Chennai, India. The findings reveal that students benefit significantly from a cohesive approach that mirrors real-world language use, improving their fluency and accuracy across all language domains. Results also indicate that integrating language skills helps learners develop balanced linguistic competence, reinforcing the interconnectedness of listening, speaking, reading, and writing. Based on these findings, this paper advocates for the redesign of educational curricula and teaching programs to adopt this integrative method, thereby improving the efficacy of Arabic language instruction for non-native speakers. The conclusion underscores that such an approach is vital for fostering communicative competence and linguistic development among learners.